2022
DOI: 10.1155/2022/8285084
|View full text |Cite
|
Sign up to set email alerts
|

CCL-2 and CXCL-8: Potential Prognostic Biomarkers of Acute Kidney Injury after a Bothrops atrox Snakebite

Abstract: In the Brazilian Amazon, the snake Bothrops atrox is the primary cause of snakebites. B. atrox (BaV) venom can cause systemic pathophysiological changes such as acute kidney injury (AKI), which leads to the production of chemokines and cytokines in response to the envenomation. These soluble immunological molecules act by modulating the inflammatory response; however, the mechanisms associated with the development of AKI are still poorly understood. Here, we characterize the profile of these soluble immunologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“…Many authors showed that the activation of renal vascular endothelium promoted the production of immunological CXC chemokine molecules. Take CXCL8 for a example, it was proved to recruit the neutrophils, assisting the activation of inflammatory pathways in the ischemic kidney and culminating the acute kidney injury [ 88 ]. As another proinflammatory gene, CXCL5 also makes the similar effect on renal inflammation and impairment of kidney function as CXCL8 [ 89 ].…”
Section: Cxcl Family and Diseasesmentioning
confidence: 99%
“…Many authors showed that the activation of renal vascular endothelium promoted the production of immunological CXC chemokine molecules. Take CXCL8 for a example, it was proved to recruit the neutrophils, assisting the activation of inflammatory pathways in the ischemic kidney and culminating the acute kidney injury [ 88 ]. As another proinflammatory gene, CXCL5 also makes the similar effect on renal inflammation and impairment of kidney function as CXCL8 [ 89 ].…”
Section: Cxcl Family and Diseasesmentioning
confidence: 99%
“…This excessive inflammatory response may have clinical consequences. Increased MCP-1 level was associated with a AKI in B. atrox envenomation in the Brazilian Amazon [88]. However, more studies are needed to identify inflammatory biomarkers predictive of the prothrombotic risk in the time-course of Bothrops envenomation, even after antivenom administration.…”
Section: Discussionmentioning
confidence: 98%
“…The cytokine IL-10 is characterized as a key molecule in the regulation of the immune response, which is capable of suppressing the activation of neutrophils and monocytes, and, consequently, the production of chemokines and cytokines, thus regulating the inflammatory processes and cytotoxic pathways [ 53 , 54 ]. Our data from the integrative analysis of the immunological molecules demonstrated the effective participation of IL-10, with several interactions established before and after the administration of antivenom in the MILD group compared with the SEV group, which may be related to the lower severity in these patients ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%